TRENDS IN UPDATING MUSIC LESSONS TAUGHT IN SECONDARY SCHOOLS - Shoira Gaffarova Shavkatovna (European Journal of Humanities and Educational Advancements, 2023)
Methodology of teaching music at school is an important subject in the training of a future music teacher. The name of the subject clearly explains its content. That is, this subject studies the issues of education of children through the medium of music. In order to master the methodology of music education, it is necessary to include music in the school program, to understand the educational possibilities of the art of music as an object of education, and to understand the identity of the modern student. To solve the complex and multifaceted tasks of education, the science of methodology uses many other subjects in the curriculum. The historical-theoretical series of subjects helps students to understand the unique features of the art of music, the reflection of life events in musical images, and the means of musical expression